MODAL SOSIAL PENJUAL JAMU KELILING DI KECAMATAN KANDIS KABUPATEN SIAK (STUDI DI KELURAHAN SIMPANG BELUTU JALAN RAJA NEGARA) - Sulis Setiawati; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Herbal medicine is a traditional treatment that has been used for generations to maintain health, treat a disease or for beauty. But over the times, herbal medicine is considered an ancient treatment by some people, this is because there is already a more modern treatment. This modern treatment makes the presence of herbal medicine increasingly pressing and rivaled, which is feared to make herbal medicine extinct. For this reason, herbal medicine sellers create a strategy to maintain their herbal medicine business, namely through social capital. The formulation of the problem discussed in this study is how social capital among the sellers of mobile herbal medicine in Kandis sub-district. The subjects of this study were 7 people selling mobile herbal medicine, namely sellers of mobile herbal medicine who have been selling herbal medicine for more than 10 years, both those who sell and carry motorbikes. The technique of determining the informant is by using a purposive sampling technique. The method used is descriptive qualitative research method. The theory used is the theory of social capital put forward by Putnam which consists of social networks, social norms and beliefs. The results of the study can be gathered that social capital can sustain their herbal medicine business, such as networks that can help herbal sellers if they experience difficulties because they work together. Social norms that can prevent divisions between herbalists and make them directed. Trust that makes it easier for them to sell herbs, buy herbal raw materials and herbal lending. With the existence of social capital such as networks, norms and beliefs, sellers of mobile herbal medicine in Kandis sub-district can maintain herbal medicine, preserve herbs, and facilitate their work, because in managing a business done together, there is a sense of mutual help and a sense of trust that is interwoven. However, from the three social capital, there is the most powerful social capital to maintain their herbal medicine business, namely trust and weak social capital, namely social norms. Keywords: Social Capital, Herbal